The complete family office handbook : a guide for affluent families and the advisers who serve them - Rosplock, Kirby, 1974- (Hoboken, New Jersey : Wiley : Bloomberg Press, 2014)
"Everything you need to take advantage of today's most exciting new wealth management career options. It seems like ever since Oprah started hers, family offices are all the rage among today's high-net-worth individuals. Private wealth management advisory firms serving one client, or a very limited number of exclusive clients, family offices come in two flavors: single family and multifamily, with the latter operating more like a traditional wealth management practice. If you're like most financial advisors, by now you're familiar with the concept, but don't know if it's right for you and your clients, or how to break into the business. This book supplies you with answers to all your questions about this exciting new career opportunity. Demystifies the concept of the family office, clarifying who should consider joining a multi-family office or starting their own single-family office Explains what services should be rendered by a family office and what the expense to the family can be. Provides the most current knowledge, research, and cutting-edge approaches from thought leaders in the family office industry. Gives you practical tools, templates, and exercises to guide you as you envision, plan, and develop your family office"--
Introduction to the family office -- Inception of the family office: pathways to be family office -- Family wealth needs: determining your family office solution and services -- Family values, mission, and vision and the family office -- Establishing and structuring of family offices -- Advising families: developing a family office baseline -- Legal and compliance standands and practices for family offices -- Investment management and the family office -- Operations and information technology in the family office -- Talent management in the family office -- Governance issues for the family office -- Preparing succeeding generations: family education in the family office -- Family entrepreneurship and the family bank -- Legacy and philanthropy in the family office -- Globalization of the family office: international families and family offices.
Includes index.
"Explains how family offices operate, who should consider forming or joining one, and how to craft and set up a structure, purpose and vision for the office that fully serves a family's particular needs and investment goals."--Provided by publisher.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed May 7, 2014).
Keywords: Family-owned business enterprises -- Management; Finance, Personal; BUSINESS & ECONOMICS -- Personal Finance -- Money Management; Family-owned business enterprises -- Management; Family-owned business enterprises; Finance, Personal; BUSINESS & ECONOMICS -- Personal Finance -- Money Management; Family-owned business enterprises -- Management; Finance, Personal; Electronic books; Electronic books